Integrasi kearifan lokal sebagai penguatan karakter positif melalui pembelajaran apresiasi puisi bagi siswa di sekolah dasar - Cintya Nurika Irma; Noviea Varahdillah Sandi; Sidna Syahdilla; Annisa Febriani Adha Atqiya (Jurnal Komunitas Bahasa, 2023)
This study aims to describe and analyze the integration of local wisdom, positive character strengthening through learning poetry appreciation for students in elementary schools. This research includes literature research using descriptive analysis methods. Data collection is carried out by reading relevant literature in books, journals, and proceedings. Data analysis techniques consist of data reduction, data presentation, and drawing conclusions using data analysis using the Miles & Huberman model. The results showed that the realization of the integration of local wisdom through the study of poetry appreciation for students in elementary schools can be realized through actions (1) strengthening language skills directed at language skills involving students' local wisdom material, (2) literary enjoyment includes a) the stage of knowing and enjoying, b) the stage of appreciating, c) the stage of understanding, d) the stage of appreciation, and e) the stage of application, (3) social approach is directed at knowledge and habituation in comparing social problems between oneself, family, school and student community, (4) cultural enrichment is directed at knowledge and understanding of local wisdom customs, customs, methods, points of view and beliefs in local wisdom, and (5) positive character strengthening is directed at strengthening understanding of good and bad values and actualization in daily life.